Independent Determinants of Stunting Among Children Under Five Years: A Case-Control Study Using Multivariable Analysis - Islamiyati, Islamiyati; Sadiman, Sadiman; Khasanah, Sapta Aprilia; Wibowo, Wahyu Dwi Ari (Journal of Applied Nursing and Health, 2026)
Background: Stunting is a chronic growth disorder caused by long-term nutritional deficiencies and repeated infections during the first 1,000 days of life. This study aimed to identify independent determinants of stunting among children under five years in the Yosomulyo Community Health Center, Metro City, Lampung, Indonesia. Methods: An analytical observational study with an unmatched retrospective case-control design was conducted from May 6 to May 30, 2025. A total of 76 children (38 cases and 38 controls) were selected using purposive sampling. Data were collected through structured interviews and verified using Maternal and Child Health (MCH) handbooks and health records to minimize recall bias. Statistical analysis was performed using IBM SPSS Statistics version 26. Bivariate analysis was conducted using the Chi-square test, and multivariate analysis was performed using multiple logistic regression with the backward likelihood ratio method. Results: Showed that maternal anemia during pregnancy, exclusive breastfeeding, history of diarrhea, and low birth weight (LBW) were independent determinants of stunting. Maternal anemia during pregnancy was associated with stunting (AOR = 2.76; 95% CI: 1.25–6.10; p = 0.001), exclusive breastfeeding (AOR = 4.86; 95% CI: 1.80–13.10; p = 0.001), history of diarrhea (AOR = 3.42; 95% CI: 1.54–7.61; p = 0.003), and low birth weight (AOR = 2.01; 95% CI: 1.10–3.67; p = 0.010). Conclusion: stunting is influenced by both prenatal and postnatal factors, particularly maternal nutrition during pregnancy, infant feeding practices, and early-life health conditions. Strengthening maternal nutrition programs, promoting exclusive breastfeeding, preventing low birth weight, and controlling childhood infections are essential strategies for stunting prevention. Future research using larger multi-center prospective designs is recommended to confirm these findings and strengthen causal inference.